Diagnosing periprosthetic joint infections: a comparison of infection definitions: EBJIS 2021, ICM 2018, and IDSA 2013. Issue 9 (7th September 2022) - Sigmund, Irene K.; Luger, Markus; Windhager, Reinhard; McNally, Martin A.
Abstract : Aims: This study evaluated the definitions developed by the European Bone and Joint Infection Society (EBJIS) 2021, the International Consensus Meeting (ICM) 2018, and the Infectious Diseases Society of America (IDSA) 2013, for the diagnosis of periprosthetic joint infection (PJI). Methods: In this single-centre, retrospective analysis of prospectively collected data, patients with an indicated revision surgery after a total hip or knee arthroplasty were included between 2015 and 2020. A standardized diagnostic workup was performed, identifying the components of the EBJIS, ICM, and IDSA criteria in each patient. Results: Of 206 included patients, 101 (49%) were diagnosed with PJI with the EBJIS definition. IDSA and ICM diagnosed 99 (48%) and 86 (42%) as infected, respectively. A total of 84 cases (41%) had an infection based on all three criteria. In 15 cases (n = 15/206; 7%), PJI was present when applying only the IDSA and EBJIS criteria. No infection was detected by one definition alone. Inconclusive diagnoses occurred more frequently with the ICM criteria (n = 30/206; 15%) compared to EBJIS (likely infections: n = 16/206; 8%) (p = 0.029). A better preoperative performance of the EBJIS definition was seen compared with the ICM and IDSA definitions (p < 0.001). Conclusion: The novel EBJIS definition identified all PJIs diagnosed by any other criteria. Use of the EBJIS definition significantly reduced the number of uncertain diagnoses, allowing easier clinical decision-making. Cite this article: Bone Joint Res  2022;11(9):608–618.